Two‐year left ventricular systolic function of percutaneous coronary intervention vs optimal medical therapy for patients with single coronary chronic total occlusion. Issue 2 (21st January 2021) - Meng, Shuang; Qiu, Lin; Wu, Jian; Huang, Rongchong; Wang, Hui
Abstract: In this study, two‐dimensional speckle tracking echocardiography (2D‐STE) and real‐time three‐dimensional echocardiography (RT‐3DE) were applied to compare the changes of left ventricular systolic function associated with percutaneous coronary intervention (PCI) versus optimal medical therapy (OMT) in patients with single chronic total occlusion (CTO). 63 single CTO patients (age 61.88 ± 8.86 years) were examined by echocardiography and were divided into the PCI group (n = 27) and OMT group (n = 36) according to the initial treatment strategy. Two‐dimensional left ventricular ejection fraction (2D‐LVEF), two‐dimensional indexed left ventricular end‐systolic volume (2D‐LVESVI), and two‐dimensional indexed left ventricular end‐diastolic volume (2D‐LVEDVI) were measured using two‐dimensional echocardiography (2DE). Three‐dimensional left ventricular ejection fraction (3D‐LVEF), three‐dimensional indexed left ventricular end‐systolic volume (3D‐LVESVI), and three‐dimensional indexed left ventricular end‐diastolic volume (3D‐LVEDVI) were measured using RT‐3DE. Global circumferential strain (GCS) and global longitudinal strain (GLS) were measured using 2D‐STE. After 2 years of follow‐up, there were no significant differences in the 2D‐LVEF, 2D‐LVESVI, 3D‐LVEF, 3D‐LVESVI, 3D‐LVEDVI, and GCS, except for GLS ( P  = .001) between the CTO‐PCI and CTO‐OMT groups. GLS decreased significantly in OMT group ( P  = .016) in contrast with PCI group in which GLS increased significantly ( P  = .007). Left ventricular systolic function assessment using 2D‐STE showed a significant difference in GLS between CTO‐PCI and CTO‐OMT. And the patients who chose PCI revascularization at the 2‐year follow‐up had better left ventricular systolic function improvement than those who were conservatively treated with OMT.